2013
DOI: 10.1186/1471-2431-13-184
|View full text |Cite
|
Sign up to set email alerts
|

Arthrogryposis in infancy, multidisciplinary approach: case report

Abstract: Background: Arthrogryposis multiplex congenita is an etiopathogenetically heterogeneous disorder characterised by non-progressive multiple intra-articular contractures, which can be recognised at birth. The frequency is estimated at 1 in 3,000 newborns. Etiopathogenesis of arthrogryposis is multifactorial. Case presentation: We report first 26 weeks of life of a boy with severe arthrogryposis. Owing to the integrated rehabilitation approach and orthopaedic treatment a visible improvement in the range of motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 13 publications
0
40
0
Order By: Relevance
“…Rehabilitation aimed to increase shoulder ROM and lasted between 11 and 36 weeks (Azbell & Dannemiller, ; Sala et al, ). All three studies showed an improvement of 25 to 80° in shoulder flexion (Azbell & Dannemiller, ; Binkiewicz‐Glinska et al, ; Sala et al, ). For shoulder abduction, 0 to 40° of improvement was found (Azbell & Dannemiller, ; Sala et al, ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Rehabilitation aimed to increase shoulder ROM and lasted between 11 and 36 weeks (Azbell & Dannemiller, ; Sala et al, ). All three studies showed an improvement of 25 to 80° in shoulder flexion (Azbell & Dannemiller, ; Binkiewicz‐Glinska et al, ; Sala et al, ). For shoulder abduction, 0 to 40° of improvement was found (Azbell & Dannemiller, ; Sala et al, ).…”
Section: Resultsmentioning
confidence: 98%
“…Of those, Azbell and Dannemiller () measured the passive range of motion of the lateral cervical flexion and the cervical rotation of an infant and found limited cervical rotation (R 90°, L 70°) and lateral cervical flexion (R 40°, L10°) at 11 days of age. Muscle tone of the head was assessed in one study, with a finding of reduced head muscle tone at birth (Binkiewicz‐Glinska et al, ). Three of the four studies on the jaw were single‐case studies and one included 23 patients with five having jaw contractures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To effectively impact the quality of life of a child with AMC, rehabilitation should be early, comprehensive, and multidisciplinary (Binkiewicz‐Glinska et al, ). Multidisciplinary team members include the core family and multiple HCP depending on the severity of AMC (Figure ).…”
Section: Introductionmentioning
confidence: 99%